Elevated Serum Procalcitonin to Predict Severity and Prognosis of Extensive Burns. Issue 7 (14th July 2022) - Liu, Zhaoxing; Li, Dawei; Liu, Xinzhu; Zhang, Bohan; Zang, Yu; Ma, Jinglong; Zhang, Wen; Niu, Yuezeng; Shen, Chuanan
Abstract: Purpose: To analyze the factors affecting the elevation of serum procalcitonin (PCT) in patients with extensive burns, and explore its potential value in evaluating the severity and prognosis. Methods: Clinical data of 139 patients with extensive burns admitted to our burn center from January 2014 to December 2019 were retrospectively analyzed. Spearman's Rank correlation coefficient was used to analyze the factors influencing the elevated PCT levels. The predictive power of PCT for death was evaluated by receiver operating characteristic (ROC) and multiple logistic regression analysis. Results: 72 cases exhibited elevated serum PCT concentrations during the shock phase, but none of them had obvious signs of infection. PCT level in the shock phase was positively correlated with burn area, depth, degree of inhalation injury, delay in fluid resuscitation, APACHE II, and SOFA scores. The peak values of PCT during shock and infection phases were significantly higher in the non-survivors than in the survivors. The areas under the ROC curve for predicting death were 0.788 and 0.926, respectively, and 5.4 ng/mL ( OR  = 5.33) and 8.5 ng/mL ( OR  = 14.49) were the high-risk thresholds for death prediction. Conclusions: Serum PCT level in the shock phase is a potential indicator for evaluating the severity of burns, while the PCT level during the infection period can be used as an early warning indicator for severe systemic infection. High levels of PCT peaks during the shock and infection periods indicate an increased risk of poor prognosis, and targeted treatment is required accordingly.